PENGARUH SUHU DAN LAMA THAWING TERHADAP KUALITAS SPERMATOZOA KAMBING PERANAKAN ETAWA - Fitrik Fitrik; N. Supartini (BUANA SAINS, 2012)
The purpose of this study was to determine the temperature and duration of thawing optimally of frozen sperm of Etawa crossbred (PE) goats used in the implementation of IB conducted in Laboratory of Animal Health and Reproduction of BBPP Batu. The material used in this study was 48 straw of goat sperm in size of 0.25 ml from Central Artificial Insemination (BBIB) Singosari. This research method used completely randomized design (CRD) with 3x4 factorial and 4 times repeating. The first factor is temperature of thawing and the second factor is thawing duration. The results show that the temperature and duration of thawing significantly affected (P